PARTITION AND BEYOND: THE LASTING IMPACT OF MUSLIM HISTORY ON MODERN INDIA AND PAKISTAN - Saqib Ullah Khan; Jafar Nazir; Sabira Iqbal (Journal of Religion and Society, 2024)
This article examines the profound and enduring effects of Muslim history on the contemporary socio-political landscapes of India and Pakistan, with a specific focus on the pivotal event of Partition in 1947. This historical division not only redefined geographical boundaries but also left a lasting imprint on the identities, politics, and communal relationships in both nations. The analysis begins by contextualizing the rich legacy of Muslim rule in the subcontinent, which set the stage for the complexities of modern nationhood and identity. The study delves into the direct consequences of Partition, such as mass migrations, communal riots, and the reconfiguration of political and social structures in the newly formed states. It explores how these events have perpetuated communal tensions and shaped the political discourse in both countries, influencing their domestic policies and bilateral relations. The role of religion in public life, as redefined by the Partition, is also scrutinized, highlighting the differing paths India and Pakistan have taken in terms of secularism and theocracy. Further, the paper discusses the cultural and psychological impact of Partition, which manifests in literature, art, and collective memory, continuing to influence relations between different community groups and the state policies toward minorities. The long-term economic impacts on both nations, particularly in border regions, are assessed to understand the broader implications of Partition. In conclusion, "Partition and Beyond: The Lasting Impact of Muslim History on Modern India and Pakistan" provides a comprehensive overview of how historical events rooted in the era of Muslim rule have continued to affect the development and interactions of India and Pakistan, suggesting that the legacies of the past are integral to understanding the contemporary challenges and dynamics of the region. Keywords: Partition, India, Pakistan, Muslim history, communal relations, national identity, socio-political impact, legacy, cultural memory, bilateral relations.